Star Bodies and the Erotics of Suffering - Glenn, Colleen; Glenn, Colleen; Bell-Metereau, Rebecca Louise; Bell-Metereau, Rebecca Louise (Book collections on Project MUSE., 2015)
The authors "assemble thirteen scholars to consider fourteen stars whose careers have been defined by suffering on- or off-screen. Together, these essays question assumptions that an actor's ability to project an enduring image-both symbolic and physical-is necessary for box-office success, demonstrating instead that disruptions often shape and direct the star image. Contributors in this collection examine a wide range of stars from the last seventy years. Some essays deal with actors who have transformed temporarily for a role, or permanently, through aging or accident, such as Joaquin Phoenix, Daniel Day-Lewis, Mickey Rourke, Charlize Theron, and Hilary Swank. Other essays consider stars' attempts to conceal aspects of themselves from the public in order to maintain a palatable public image, including Rita Hayworth, Rock Hudson, and Michael Jackson. Some explore typecasting and audience expectations, noting how struggles with marriage, divorce, and aging intersect in the images of Natalie Wood, Marilyn Monroe, and Harrison Ford. A final set considers Sissy Spacek, Julia Roberts, and Halle Berry as women who reconfigure negative press and restrictive gender and racial expectations to their advantage, managing public perceptions of suffering in ways that flummox their critics"--Amazon.com.